Conjugated helical polymers: End-group control and coupling reactions. (12th March 2019) - Kamada, Takeru; Miyagi, Yu; Sanda, Fumio
Abstract: Telechelic helical poly(phenyleneethynylene)s2 and3 bearing end iodo and ethynyl groups were synthesized by the Sonogashira–Hagihara coupling reaction of prepolymer1 with N -α- tert -butoxycarbonyl-3, 5-diiodo-4-hydroxy-d -phenylglycine hexylamide (4 ) and p -diethynylbenzene (5 ), respectively. Polymer2 was treated by Sonogashira–Hagihara coupling reaction with 1, 6-diethynylpyrene (a ) and 4, 4-diethynylbiphenyl (b ) to obtain the corresponding polymers2a and2b . Polymer2 was also subjected to the Mizoroki–Heck coupling reaction with diphenyl( p -vinylphenyl)phosphine (e ) to obtain the corresponding polymer2e, and the incorporation of the phosphine moieties was confirmed by 31 P NMR spectroscopy. In a similar fashion, polymer3 was polymerized with 1, 4-dibromonaphthalene (c ) and 9, 10-dibromoanthracene (d ), but no concrete evidence for the formation of polymers3c and3d was observed. Circular dichroism (CD) spectroscopic analysis revealed that all the polymers adopted folded helical conformations with predominantly one-handed screw sense in CHCl3 . The polymers exhibited photoluminescence (PL) depending on the incorporated functional groups. Graphical abstract: Novel helically folded telechelic conjugated polymers bearing end iodo and ethynyl groups were synthesized by the Sonogashira–Hagihara couping reactions.Image 1